Blockade of Motor Cortical Long-Term Potentiation Induction by Glutamatergic Dysfunction Causes Abnormal Neurobehavior in an Experimental Subarachnoid Hemorrhage Model - Fujiki, Minoru; Kuga, Kazuhiro; Ozaki, Harushige; Kawasaki, Yukari; Fudaba, Hirotaka (Frontiers in Neural Circuits, 2021)
Subarachnoid hemorrhage (SAH) is a life-threatening condition that can also lead to permanent paralysis. However, the mechanisms underlying neurobehavioral deficits after SAH have not been fully elucidated. As theta burst stimulation (TBS) can induce long-term potentiation (LTP) in the motor cortex, we tested its potential as a functional evaluation tool after experimentally- induced SAH. Motor cortical inter-neuronal excitability was evaluated in anesthetized rats after 200 Hz-quadripulse TBS (QTS5), 200 Hz-quadripulse stimulation (QPS5), and 400 Hz-octapulse stimulation (OPS2.5). Furthermore, correlation between motor cortical LTP and N-methyl-D-aspartateNMDA--receptor activation was evaluated using MK-801, an NMDA-receptor antagonist. We evaluated inhibition-facilitation configurations (interstimulus interval: 3 ms; short-latency intracortical inhibition [SICI] and 11 ms; intracortical facilitation [ICF]) with paired electrical stimulation protocols and the effect of TBS paradigm on continuous recording of motor-evoked potentials (MEPs) for quantitative parameters. SAH and MK-801 completely blocked ICF, while SICI was preserved. QTS5, QPS5, and OPS2.5 facilitated continuous MEPs, persisting for 180 min. SAH and MK-801 completely blocked MEP facilitations after QPS5 and OPS2.5, while MEP facilitations after QTS5 were preserved. Significant correlations were found between neurological scores and 3 ms-SICI rates, 11 ms-ICF rates, and MEP facilitation rates after 200 Hz-QTS5 7 days after SAH (R² = 0.6236; r= -0.79, R² = 0.6053; r=-0.77 and R² = 0.9071; r= 0.95, p< 0.05, respectively). Although these findings need to be verified in humans, our study demonstrates that the neurophysiological parameters 3 ms-SICI, 11 ms-ICF, and 200 Hz-QTS5-MEPs may be useful surrogate quantitative biomarkers for assessing inter-neuronal function after SAH.